ATIM-27. INTRATUMORAL ADMINISTRATION OF AN ONCOLYTIC POLIO/RHINOVIRUS RECOMBINANT (PVSRIPO) IN MALIGNANT GLIOMA PATIENTS: ASSESSMENT OF MUTATIONAL RESPONSE CORRELATES. (5th November 2018) - Ashley, David; Desjardins, Annick; Gromeier, Matthias; Muscat, Andrea; Herndon, James; Friedman, Allan; Friedman, Henry; McSherry, Frances; Randazzo, Dina; Peters, Katherine; Threatt, Stevie; Bullock, Chevelle; et al.
Abstract: BACKGROUND: The live attenuated oral poliovirus vaccine was modified to contain a heterologous internal ribosomal entry site stemming from human rhinovirus type 2, creating PVSRIPO. PVSRIPO recognizes CD155, an oncofetal cell adhesion molecule and tumor antigen widely expressed ectopically in malignancy. We report results of the dose finding trial evaluating PVSRIPO delivered intratumorally by convection-enhanced delivery (CED). METHODS: Eligible patients were adults with recurrent supratentorial WHO grade IV MG; solitary tumor 1–5.5cm in diameter; 4 weeks after chemotherapy, bevacizumab or study drug; adequate organ function; KPS70%; and positive anti-polio titer. RESULTS: A total of 61 pts were treated on study. Only one DLT was observed, a grade 4 intracranial hemorrhage at the time of catheter removal on DL5. Study related adverse events consisted of localized peritumoral inflammation, triggering neurologic symptoms in relation to the location of the infused tumor. Of the 26 patients treated more than 36 months ago, six are alive at 73.6+, 72.5+, 60.6+, 44.0+, 39.3+, and 36.9+ months. Deep sequencing of biopsy material obtained prior to PVSRIPO infusion in 31 samples, confirmed that a very low mutational load is associated with longer survival (p=0.017). Additionally, no patients whose tumors had >0.5 non-synonymous mutations per Mb survived beyond 18 months. CONCLUSION: Infusion of PVSRIPO via CED is safe and encouraging efficacy results were observed in adults along with mutational correlates of response.